Influência do ciclo ovariano na ação aguda do Diazepam em mulheres submetidas a um modelo de ansiedade experimental - Almeida, Camila Danielle Aragão (2013)
Several studies have shown the influence of ovarian hormones on the GABAergic system. As women are naturally exposed to monthly fluctuation of these hormones, it is possible that their response to benzodiazepnes also change over the ovarian cycle. Considering that anxiety disorders are most common in women and therefore they receive more prescriptions for benzodiazepines, this study aimed to evaluate the possible influence of the ovarian cycle of healthy women on the acute effect of diazepam. For that, 40 subjectively healthy women were selected and allocated to two different groups, according to their ovarian cycle phase (follicular or luteal). Both groups were submitted to the Video-Monitored Stroop Color-Word Test (VMSCWT), an experimental model of anxiety, under the influence of diazepam (10 mg) or placebo. Psychological parameters (subjective scales of anxiety) and physiological parameters (heart rate and gastrocnemius electromyogram) were evaluated throughout the test. The results showed that, in the follicular phase, women did not respond to the anxiolytic action of diazepam, although a sedative effect was observed, while in the luteal phase, there was no response to either sedative or anxiolytic actions. As a control of the experimental conditions, a group of 18 men was also submitted to the VMSCWT. The results confirmed that both the anxiogenic test and the administered drug were working as expected, since diazepam managed to prevent the anxiety induced by the test. Therefore, the present findings indicate that the ovarian cycle can alter the effects of the acute administration of diazepam, which can vary from no effect to sedation, without going through anxiolysis